In vitro and in vivo Anti-Tumor Effects of Pan-HER Inhibitor Varlitinib on Cholangiocarcinoma Cell Lines - Dokduang H; Jamnongkarn W; Promraksa B; Suksawat M; Padthaisong S; Thanee M; Phetcharaburanin J; Namwat N; Sangkhamanon S; Titapun A; Khuntikeo N; Klanrit P; et al. (Dove Medical Press, 2020)
Hasaya Dokduang,1,2 Wassana Jamnongkarn,1,2 Bundit Promraksa,2,3 Manida Suksawat,3 Sureerat Padthaisong,2,3 Malinee Thanee,1,2 Jutarop Phetcharaburanin,1– 3 Nisana Namwat,1– 3 Sakkarn Sangkhamanon,2,4 Attapol Titapun,1,2,5 Narong Khuntikeo,1,2,5 Poramate Klanrit,1– 3 Watcharin Loilome1– 3 1Cholangiocarcinoma Screening and Care Program (CASCAP), Faculty of Medicine, Khon Kaen University, Khon Kaen 40002, Thailand; 2Cholangiocarcinoma Research Institute, Khon Kaen University, Khon Kaen 40002, Thailand; 3Department of Biochemistry, Faculty of Medicine, Khon Kaen University, Khon Kaen 40002, Thailand; 4Department of Pathology, Faculty of Medicine, Khon Kaen University, Khon Kaen 40002, Thailand; 5Department of Surgery, Faculty of Medicine, Khon Kaen University, Khon Kaen 40002, ThailandCorrespondence: Watcharin LoilomeDepartment of Biochemistry, Faculty of Medicine, Khon Kaen University, Khon Kaen 40002, ThailandTel/Fax +66 43 348 386Email watclo@kku.ac.thBackground: Cholangiocarcinoma (CCA) is a slowly progressing but highly aggressive malignancy. Targeting the HER protein family represents a potential therapeutic strategy for CCA treatment. The pan-HER inhibitor varlitinib is being developed for the treatment of breast cancer, gastric cancer, and biliary tract cancer, which includes CCA. This study aims to evaluate the anti-tumor effect of varlitinib on CCA using both in vitro and in vivo models.Materials and Methods: HER family expression profiles and the cytotoxic activity of varlitinib were determined in CCA cell lines (KKU-214, KKU-213, KKU-156 and KKU-100) and cholangiocyte (MMNK-1). Anti-proliferation and apoptosis induction were examined in KKU-214 and KKU-100 cell lines. A combination of varlitinib with PI3K inhibitor, BKM-120, was explored for efficacy in the KKU-100 cell line. In addition, the anti-tumor activity of varlitinib on CCA and the key metabolites were evaluated in tumor tissues from CCA xenograft model.Results: Elevated expressions of EGFR and HER2 were observed in KKU-214 and KKU-100 cells and varlitinib can suppress CCA cell growth in the micromolar range. Varlitinib inhibits cell proliferation and enhances cell death via the suppression of Akt and Erk1/2 activity in the KKU-214 cell line. While KKU-100 cells showed a poor response to varlitinib, a combination of varlitinib with BKM-120 improved anti-tumor activity. Varlitinib can significantly suppress tumor growth in the CCA xenograft model after oral administration for 15 days without noticeable toxicity, and aspartate can be the key metabolite to correlate with varlitinib response.Conclusion: Our study indicates that varlitinib is a promising therapeutic agent for CCA treatment via the inhibition of EGFR/HER2. The anti-tumor effect of varlitinib on CCA also showed synergism in combination with PI3K inhibition. Aspartate metabolite level was correlated with varlitinib response. Combination of varlitinib with targeted drug or cytotoxic drug was recommended.Keywords: cholangiocarcinoma, varlitinib, pan HER inhibitor, HER receptor family